Family Assistance for Treatment of Developmental Psychomotor Defects in Children with ASD - Ionova S. A. (Socio-Cultural and Psychological Problems of the Modern Family: Current Issues of Assistance and Support, 2020)
the article is devoted to the study of the family's role in the correction process of psychomotor development in children with Autism Spectrum Disorders. Based on the analysis of pedagogical, psychological and specialized medical literature, the article reveals the specificity of the family work with a child. The description of the pedagogical and psychological strategies of work with the child with ASD to correct the psychomotor disorders is particularly important. It's pointed out that the necessity of including the families is important in the correction process.
Keywords: коррекция; семья; family; correction; расстройства аутистического спектра; психомоторное развитие; стратегии; autism spectrum disorders; psychomotor development; strategies